Microsoft Access 2010 : a case approach : - O'leary, Timothy J. (McGraw Hill, 2011)
Office 2010: A Case Approach offers running case study throughout the text to help students understand the material in a consistent, relevant environment. Through this theme of “Making Office Relevant,” this text helps students understand why they need this course and these skills. Student success is assured through clear step-by-step instruction, plentiful screen captures and conceptual explanations